Space invaders. (Economist, 2012)
The article focuses on competition between semiconductor chip companies Intel and ARM. It comments on differences in chip designs between the two companies, with Intel chips maximizing processing power while ARM chips economize on energy. It talks about ARM's federated business design and the history behind ARM's position in the mobile device market. It mentions that Intel is making inroads on the mobile device market while ARM is developing servers that utilize ARM chips.